(untitled) (REMUNOM, 2025)
The right to housing is expressly guaranteed by the 1988 Federal Constitution and must be ensured through urban public policies that reduce inequalities in access to urban spaces. In this context, Law No. 13,465/2017 (the Land Regularization Law) emerged in mid-2017, introducing unprecedented legal mechanisms such as land tenure legitimization and the real right to slab ownership. Accordingly, this article aims to analyze the impacts of this law and examine its significance as an instrument for the realization of this fundamental right. As for the methodology, this study consists of a literature review based on analytical-exploratory research conducted through books, scientific articles, and legal provisions related to the topic. In conclusion, it is found that Law No. 13,465/2017 was a significant milestone in advancing land regularization in Brazil and, consequently, in enforcing the right to housing.